2011
DOI: 10.1016/j.bpc.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Global architecture of human poly(A)-specific ribonuclease by atomic force microscopy in liquid and dynamic light scattering

Abstract: Deadenylation is the initial and often rate-limiting step in the main pathways of eukaryotic mRNA decay. Poly(A)-specific ribonuclease (PARN) is a eukaryotic enzyme that efficiently degrades mRNA poly(A) tails. Structural and functional studies have shown that human PARN is composed of at least three functional domains, i.e. the catalytic nuclease domain and two RNA binding domains, the R3H and the RNA recognition motif (RRM), respectively. However, the complete structure of the full length protein is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…5. This hypothesis is consistent with the previously AFM result, which showed that the full-length PARN has a compact globular architecture [13]. The interaction interface between CTD and the RNA-binding domains did not interfere with the binding sites of substrate and allosteric regulators [22] but enhanced domain stability against heat-induced inactivation (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5. This hypothesis is consistent with the previously AFM result, which showed that the full-length PARN has a compact globular architecture [13]. The interaction interface between CTD and the RNA-binding domains did not interfere with the binding sites of substrate and allosteric regulators [22] but enhanced domain stability against heat-induced inactivation (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…[5]). However, little is known about CTD of PARN, which contains about 120 amino acid residues and is predicted to be intrinsically unstructured [13,14]. The existence of two PARN proteolytic fragments with the removal of CTD in Xenopus and HeLa cell extracts [24,25] implies that CTD may have regulatory roles in the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major dimerization surface is formed by the nuclease domain, and mutations disrupting it strongly reduce enzymatic activity [41]. The C-terminal $130 amino acids are predicted to be unstructured but may contain a second dimerization surface [43]. As a member of the DEDD superfamily of 3 0 exonucleases described earlier [40,41,44,45], PARN degrades RNA from the 3 0 end, releasing 5 0 -NMPs.…”
Section: Discovery Structure and Catalytic Propertiesmentioning
confidence: 99%
“…PARN exists as a dimer with the exonuclease domain acting to coordinate the two subunits [16]. The dimeric structure of PARN has been determined by X-ray crystallography of partial proteins [17], analytical ultracentrifugation [16], and in solution for the entire protein by atomic force microscopy and dynamic light scattering [18]. PARN requires divalent cations, particularly Mg 2+ , for optimal enzymatic activity [19].…”
Section: Parn (Poly (A)-specific Ribonuclease)mentioning
confidence: 99%